2019
DOI: 10.3389/feart.2019.00030
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics of Methane and Carbon Dioxide Evasion From an Open System Pingo: Lagoon Pingo, Svalbard

Abstract: The processes associated with the release of CH 4 and CO 2 from sub-permafrost groundwaters are considered through a year-long monitoring investigation at a terrestrial seepage site in West Spitsbergen. The site is an open system pingo thought to be associated with the uplift of a former sea-floor pockmark in response to marked isostatic recovery of the coastline following local ice sheet loss over the last 10,000 years. We find that locally significant emissions of CH 4 and (less so) CO 2 to the atmosphere re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(100 citation statements)
references
References 32 publications
1
99
0
Order By: Relevance
“…Presumably, during that time, groundwater flow through the permafrost continued, but instead of discharging to the surface, groundwater froze within the pingo and added to its growth. From Lagoon Pingo, Yoshikawa and Harada (1995) reported a spring discharge of 0.013 to 0.016 L s -1 , Hodson et al (2019)…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, during that time, groundwater flow through the permafrost continued, but instead of discharging to the surface, groundwater froze within the pingo and added to its growth. From Lagoon Pingo, Yoshikawa and Harada (1995) reported a spring discharge of 0.013 to 0.016 L s -1 , Hodson et al (2019)…”
Section: 3mentioning
confidence: 99%
“…Pingo spring waters and sub-permafrost groundwater in Adventdalen indeed contain both CH 4 and CO 2 (Hodson et al, In Review). The methane is dominated by a biogenic fingerprint (Hodson et al, 2019) and contemporary methanogenesis is probable (Huq et al, 2017). In order to explain pressure build-up, the essential question is whether any ongoing process produces or releases gas to the groundwater, thereby increasing pressure.…”
Section: Equilibration To Ongoing Perturbationsdensity Contrasts and mentioning
confidence: 99%
“…We note that the equilibrium concentration of dissolved methane for spring waters remaining in contact with the atmosphere's background CH 4 concentration of ~1900 ppb is very low (< 1 x 10 -4 mg L -1 ) compared to the observed concentrations, and so the emission flux can be crudely estimated from the product of the pingo outflow rates and their average methane concentration. This is justifiable because outflows are visibly uniform throughout much of the year, even during winter, when emissions continue following the thermal cracking and hydrofracture of the ice lid (see Hodson et al, 2019).…”
Section: Pingos and Springs As Methane Emission Hotspotsmentioning
confidence: 99%
“…This permafrost aggradation increases hydraulic pressure and thus forces residual groundwater toward the land surface. Since the hydraulic conductivity of the fine-grained, uplifted marine sediments is very low (Hornum et al, 2020), the fluids are likely to exploit any former pockmarks that are uplifted with them (e.g. Hodson et al, 2019).…”
Section: The Field Sitementioning
confidence: 99%
“…Further, Pohlman et al (2017) have shown that sea floor gas emissions in coastal waters off Svalbard may also be offset by far greater rates of atmospheric CO 2 sequestration into the overlying surface waters because the rising bubbles help nutrient-rich bottom waters rise up to fuel the photosynthesising plankton community. However, Hodson et al (2019) showed that pockmarks exposed by isostatic uplift have the potential to form methane seepage pathways on land. Since any groundwater carrying the gas through the permafrost will be subject to freezing temperatures, these features are likely to become discernible as small, ice-cored hill forms known as open-system pingos ( Fig.…”
Section: Introductionmentioning
confidence: 99%